A new Pseudopyrochroa Pic, 1906 from Yunnan, China with a key to adultPseudopyrochroa males from the Province and correction on type repository for Frontodendroidopsis pennyi Young (Coleoptera: Pyrochroidae: Pyrochroinae) - Young, Daniel K. (Zootaxa, 2019)
A new species of the fire-colored beetle genus Pseudopyrochroa Pic, 1906, is described from northwestern Yunnan Province, China. The new species, Pseudopyrochroa grzymalae, is superficially similar to P. cardoni (Fairmaire), known from Kashmir and Sikkim. A complete species diagnosis is presented along with a key to adult males of the five known Yunnan Pseudopyrochroa species. The repository for the holotype of Frontodendroidopsis pennyi Young is corrected from the California Academy of Sciences to the Institute of Zoology, Bejing.